2018
DOI: 10.11114/jets.v6i4.3040
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Digit Ratio (2D:4D) With Cerebral Lateralization and Grip Strength in Elite Swimmers

Abstract: The index finger and the 4th finger ratio (2D:4D) is the indicator of the prenatal testosterone. The aim of this study is to investigate the relationship between 2D:4D, hand preference and hand grip strength in swimmers. A total of 80 elite swimmers, participated in the study. Height, body weight, body mass index (BMI), hand 2D:4D finger measurements and hand grip strength tests were performed for athletes. The hand preference was determined by the Oldfield questionnaire and it was evaluated according to the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 25 publications
0
11
1
2
Order By: Relevance
“…When right hand 2D:4D and left hand 2D:4D average values were compared in the sedentary group, no statistically significant difference was found, while significant difference was found in athletes. Statistically significant difference was found between right and left hand 2D:4D ratios in elite male swimmers in Acar and Eler (2018)'s study and in male taekwondo athletes in Kim [23]'s study (p<0.05). In the present study and in Kim (2016)'s study, left hand 2D:4D ratios are lower when compared with right hand 2D:4D ratios.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…When right hand 2D:4D and left hand 2D:4D average values were compared in the sedentary group, no statistically significant difference was found, while significant difference was found in athletes. Statistically significant difference was found between right and left hand 2D:4D ratios in elite male swimmers in Acar and Eler (2018)'s study and in male taekwondo athletes in Kim [23]'s study (p<0.05). In the present study and in Kim (2016)'s study, left hand 2D:4D ratios are lower when compared with right hand 2D:4D ratios.…”
Section: Discussionmentioning
confidence: 89%
“…Hill et al, (2012), (n=41) found no significant relation between maximal oxygen uptake and right or left 2D:4D. Acar and Eler (2018), found negative correlation between right and left hand 2D:4D and both dominant and non-dominant hand grip strength of elite men swimmers. , also found negative correlation between right and left hand 2D:4D and both dominant and non-dominant hand grip strength of men elite handball players.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, the methodology of "2D: 4D" was also used by other specialists [46,[48][49][50][51][52]. Kamińska and Szymańska-Parkieta [53] studied a large group of schoolgirls of 13 years old and found that in physically more developed girls, the proportions of the fingers were close to male.…”
Section: Discussionmentioning
confidence: 99%
“…14 Sportif performans ile sağ-sol 2D:4D arasında, yalnızca sağ 2D:4D arasında ilişki olduğunu, ne sağ ne sol 2D:4D arasında ilişkinin olmadığını ya da yalnızca sağ 2D:4D ile sol 2D:4D arasındaki ilişkiyi inceleyen birçok çalışma bulunduğu bilinmektedir. 15,16 Hönekopp ve ark. yaptıkları çalışmada 2D:4D ile performans arasında kadınlarda sol elde, erkeklerde ise sağ elde düşük ilişki tespit edilmiş, diğer bir çalışmada ise sadece erkeklerde sol 2D:4D arasında, Fink ve ark., erkeklerde 2D:4D ve el kavrama kuvveti arasında; Eler ve Eler, erkeklerde sağ-sol 2D:4D, kadınlarda yalnızca sol 2D:4D arasında; Acar ve Eler erkek ve kadınlarda negatif yönlü ilişki olduğunu ifade etmişlerdir.…”
unclassified